Boosting Departmental Performance: The Role of Empowerment, Productivity and Faculty Engagement - Handini, Mia; Sugiono, Edi; Hasanudin, E. (International Review of Management and Marketing, 2026)
The study aims to assess the effect of Faculty Productivity (PR) and Faculty Empowerment (EM) influence Departmental Performance (DP) within private higher education institutions in DKI Jakarta, Indonesia. It specifically explores the extent to which Faculty Engagement (EG) bridges these relationships, providing empirical insights into the drivers of organizational success where research gaps currently exist in the private higher education landscape. This study use a quantitative research using the survey instrument that was measured with a 6-point Likert scale, which ranged from 1 (strongly disagree) to 6 (strongly agree). A total of 300 questionnaires were randomly distributed to the departmental heads at private higher education institutions in DKI Jakarta using a random sampling technique. From the distributed questionnaires, 228 valid responses were obtained, providing a substantial sample for analysis. To examine the relationships within the conceptual framework, the study utilized the Partial Least Squares (PLS-SEM) technique for rigorous data processing. Empirical evidence demonstrates that faculty empowerment and faculty productivity exert a substantial positive influence on departmental performance. Moreover, the results substantiate the role of faculty engagement as a critical mediator, acting as a catalyst that reinforces the link between empowerment, productivity, and the cumulative success of academic units.